Effect of cutting parameters on the hole diameter and surface roughness for dry drilling of aluminum alloy 6061 - Ahamed, Ahmad Fauzi (2010)
Green manufacturing and sustainability are becoming very important issues in today technologies. Besides, dry machining represents cost saving opportunities related to cooling lubrication. In addition, drilling holes is one of the major manufacturing processes which include a wide range of products. The objective of this work was to find out the optimum cutting parameters to optimize the surface roughness of the hole and its diameter accuracy in the dry drilling process based on the selected setting parameters. The selected material for this study was Aluminium alloy 6061. The selected cutting parameters for this study were the cutting speed, feed rate, and the hole depth. The effect of these parameters on the hole diameter accuracy and its surface roughness are measured and analyzed. Experiments were conducted based on Design of Experiment (DOE), and the analysis of variance (ANOVA) is employed to find the optimal level and to analyze the effect of the drilling parameters on surface roughness and hole diameter accuracy values. Result shown that cutting parameters have the significant effect to the hole diameter and for surface roughness all the three parameters have the significant effect. Confirmation tests were conducted in order to validate the test result.